Analysis of the model using General Evolutionary Algorithm - N. Hu (INTERNATIONAL JOURNAL ENGINEERING AND APPLIED TECHNOLOGY (IJEAT), 2018)
The study aims to solve the universality of evolutionary computation for solving different optimization problems, avoid the repeating design, and share codes, so as to improve the application efficiency of the algorithms. To achieve this, the authors put forward a general evolutionary model based on object-oriented programming language (C# language) in this paper. This model divides the problem domain, the fitness function, the algorithm and the parameter control into different classes, which are encapsulated into different objects so as to enhance the independence of each module. By utilizing the model, it is convenient to develop, reuse, extend and modify software while guaranteeing the universality of the algorithm at the same time.